German romanticism as a predecessor to Ferdinand de Saussure's thought - Román-Gamboa, Kevin (2023)
This paper deals with some plausible links between German Romanticism thinkers and Saussure’s thought. In particular, I examine texts of Schleiermacher, Novalis, and W. Humboldt. F. Saussure’s main text employed is the Cours de linguistique générale (1916). Likewise, Albertine Necker de Saussure (F. Saussure’s great aunt) is taken into account as a relevant thinker in the relation F. Saussure-Romanticism.